KOMPETENSI APARATUR SIPIL NEGARA DI ERA DIGITAL SEBUAH KERANGKA KONSEPTUAL - Trisno Sakti Herwanto; Hasbi Rohmansyah; Anastasia Kade Daga; Bernadeth Getrudis Roflebabin (Kebijakan : Jurnal Ilmu Administrasi, 2024)
The competency of State Civil Apparatus (ASN) in the digital era is increasingly important to study as the phenomenon develops that the future of public bureaucracy is increasingly linked to the use of digital technology. However, efforts to form a conceptual framework regarding these competencies are still very minimal. Based on this gap, this paper is directed at formulating a conceptual framework for ASN competency in the digital era. It is hoped that this effort will be useful for developing public sector HR management activities with a digital perspective. To formulate the conceptual framework, a literature review was carried out on various scientific documents that were in accordance with the focus of the article. This process succeeded in building a conceptual framework regarding ASN competency in the digital era which consists of two major competencies, namely public service competency and digital competency. Public service competencies include social maturity, practical skills, and knowledge abilities, while digital competencies include e-government, digital transformation, cybersecurity, data analytics, smart cities, telecommunications, and public participation.